An Exploration of the Calls Received by the Kentucky Council on Problem Gambling Help Hotline - Jones, Carleigh (2011)
Studies that focus on crisis hotlines are abundant, however very few deal with the subject of gambling. The literature reviewed examines gambling as an addiction and the general existence of hotlines. This study examines the use of the hotline provided by the Kentucky Council on Problem Gambling (KYCPG) in a dichotomous breakdown of gender. There are some significant differences between males and females, particularly regarding criminal behavior in the effort to recoup gambling losses or to continue gambling. An additional breakdown of seasonal and regional call logs further analyzes the use of the KYCPG hotline